A simple electrochemical platform based on pectin stabilized gold nanoparticles for picomolar detection of biologically toxic amitrole1. Issue 16 (21st August 2015) - Mani, Veerappan; Devasenathipathy, Rajkumar; Chen, Shen-Ming; Vasantha, V. S.; Ajmal Ali, M.; Huang, Sheng-Tung; Al-Hemaid, Fahad M. A.
<x xml:space="preserve">Abstract</x> Amitrole adsorption on calcium cross-linked pectin stabilized gold nanoparticles for ultrasensitive detection of amitrole.